Terahertz bremsstrahlung and frequency comb induced by variable motion of an antiferromagnetic domain wall. (21st July 2022) - Ge, Xu; Chen, Yangyi; Cao, Yue; Li, Can; Li, Tailin; Li, Ziquan; You, Long; Liang, Shiheng; Yang, Xiaofei; Zhang, Yue
Abstract: We numerically investigate the emission of spin wave (SW) packets from an antiferromagnetic (AFM) domain wall (DW) moving at a varying velocity. This SW is analogous to the bremsstrahlung of a charge with variable motion. The SW packets are emitted towards both sides of DW in the DW acceleration/deceleration process. The frequency of this bremsstrahlung-type SW is at sub-terahertz (THz), which is one magnitude lower than that of SW emitted by the Lorentz contraction of DW. Based on the bremsstrahlung-type SW, we proposed a frequency comb with a sub-THz central frequency and a GHz frequency interval by exploiting the back-and-forth DW variable motion. Our work paves a way for developing a spin–orbit-torque -based AFM THz device with a tunable frequency band.